(untitled) (ENTHYMEMA, 2012)
In this paper, the author presents a detailed scenario of artistic and political movements characterising visual culture since 1968, focusing in particular on the Milanese area. The analysis dwells upon a series of progressive and stimulating events that attempted to overturn the artistic cultures of that time through the rise of groups and collectives. This turmoil would find a fertile soil until 1977-1978. According to the author, this biennium corresponded with a gradual re-birth of autonomous artists and of ‘new groups’.